2013
DOI: 10.1111/ejn.12417
|View full text |Cite
|
Sign up to set email alerts
|

Posterior parietal cortex is critical for the encoding, consolidation, and retrieval of a memory that guides attention for learning

Abstract: Within most contemporary learning theories, reinforcement prediction error, the difference between the obtained and expected reinforcer value, critically influences associative learning. In some theories, this prediction error determines the momentary effectiveness of the reinforcer itself, such that the same physical event produces more learning when its presentation is surprising than when it is expected. In other theories, prediction error enhances attention to potential cues for that reinforcer by adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 90 publications
4
49
0
Order By: Relevance
“…Finally, we have identified several regions that are critical to the expression of enhanced associability in faster learning but not to the original encoding of altered associability, including substantia innominata/nucleus basalis magnocellularis, the secondary visual cortex, the dorsolateral striatum, and the lateral hypothalamus. Circuitry by which recalculated associability values are conveyed to PPC for storage and by which these altered associability memories are transmitted to components of the expression module remains a subject of speculation (Schiffino, 2015; Schiffino, Zhou, & Holland, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have identified several regions that are critical to the expression of enhanced associability in faster learning but not to the original encoding of altered associability, including substantia innominata/nucleus basalis magnocellularis, the secondary visual cortex, the dorsolateral striatum, and the lateral hypothalamus. Circuitry by which recalculated associability values are conveyed to PPC for storage and by which these altered associability memories are transmitted to components of the expression module remains a subject of speculation (Schiffino, 2015; Schiffino, Zhou, & Holland, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Post-surprise infusions of anisomycin, lidocaine, or muscimol prevented subsequent display of surprise-enhanced associability. Because previous studies indicated that CeA function is unnecessary for the expression of associability enhancements that were induced previously when CeA function was intact (Holland & Gallagher, 2006), we interpreted these results as indicating that post-surprise activity of CeA (“surprise replay”) is necessary for the consolidation of altered associability memories elsewhere in the brain, such as the posterior parietal cortex (Schiffino, et al, 2014a). …”
mentioning
confidence: 87%
“…Interestingly, Schiffino et al (2014a) found that function of the posterior parietal cortex (PPC) was critical at both the time of surprise and the time of expression. Because PPC function was required both when surprise-induced changes in associability were encoded and when they were retrieved for new learning, Schiffino et al (2014a) suggested that PPC might be the site of a relatively permanent memory of altered cue associability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations